328 First-to-second progression-free survival ratio as a predictor for overall survival in ovarian cancer. (18th September 2019) - Salman, L; Gandelsman, E; Romano, A; Sabah, G; Jakobson-Setton, A; Borovich, A; Yeoshoua, E; Eitan, R
Abstract : Objectives: We aimed to evaluate the impact of first-to-second progression free survival (PFS1/PFS2) ratio on overall survival (OS) in patients with ovarian cancer. Methods: A retrospective cohort study of all patients with ovarian carcinoma treated in one university-affiliated medical center (2000–7/2017). We included patients who had at-least a second recurrence. We included patients who were initially platinum sensitive, therefore patients with first progression-free survival (PFS) less than 12 months were excluded. Study groups included patients with PFS1/PFS2 <1.0 and patients with PFS1/PFS2 ≥1.0. Demographics and treatment outcomes were compared between groups. The primary outcome was OS. In addition, we assessed the linear correlation between first and second PFS. P value <0.05 was considered significant. Results: Overall, 65 patients met inclusion criteria. In this cohort, the mean of first PFS was 64.6±54.3 months, and the mean for the second PFS was 20.8±32.4. Overall, 13 (20%) had PFS1/PFS2 <1.0 and 52 (80%) had PFS1/PFS2 ≥1.0. Patients in the PFS1/PFS2 <1.0 group were younger, although not reaching statistical significance (median age 48 vs. 59 years, p=0.05). There were no significant difference in stage of disease or histology. There were no difference in rates of neoadjuvant chemotherapy between groups (15.4% vs 34.6%, p=0.31). In a Kaplan-Meier analysis, there were no difference between groups in OS (figure 1 ). Using Pearson's Correlation coefficient, longer first PFS was associated with longer second PFS (r=0.3). Conclusions: In patients with ovarian cancer, longer first PFS seems to be associated with longer second PFS. However, first-to-second PFS ratio does not predict OS.